Recent advances in liquid biopsy in cancers: Diagnosis, disease state and treatment response monitoring - Zhixian Chen; Judy Wai Ping Yam (Clinical and Translational Discovery, 2022)
Abstract Recent years have witnessed the development of scientific research and clinical trials of liquid biopsy in various diseases, especially cancers. Liquid biopsy refers to a procedure in which components, including circulating tumour cells (CTCs), cell‐free nucleic acids (cfDNA and cfRNA) and small extracellular vesicles (sEVs), are obtained from blood or other biofluids for analyses. Together with other biocomponents present in liquid biopsies, including CTCs and cell‐free nucleic acids, sEVs are now hotly anticipated as analytical tools and are expected to help identify early‐stage patients and improve cancer patient survival. The independence from tissue availability further confers on liquid biopsy exclusive roles in patient follow‐up and treatment response monitoring. In the past few years, great challenges have been addressed, and remarkable progress has been made in the technologies used for the detection and collection of these biomaterials, enabling liquid biopsy to enter an increasing number of clinical trials and clinical practice. Although problems regarding accuracy and sensitivity remain to be solved, encouraging outcomes have been reported by scientists and clinicians regarding successful applications of liquid biopsy in the prediction of cancer recurrence and responsiveness to specific drugs. Additionally, according to recent reports, this new comprehensive and systematic approach of sampling and analysis shows much potential in non‐tumour fields, such as neurodegenerative and autoimmune diseases. In this review, the current state and latest developments in the applications of different components in liquid biopsy will be discussed, and the use of sEVs in this novel medical strategy will be highlighted.